Positive vaccine beliefs linked to reduced mental stress in healthcare professionals during COVID-19: a retrospective study - Lin, Yu-Yin; Cho, Shih-Feng; Hsieh, Yi-Ling; Chuang, Yun-Shiuan; Hsu, Chia-En; Liu, Yun-Chen; Sung, Chia-Chi; Huang, Ya-Hsiu; Ku, Wen; Hsieh, Meng-Hsuan; Huang, Ya-Chin; Tu, Hung-Pin; et al. (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic has led to a significant adverse effect on the mental health of healthcare professionals. This study aims to assess the effects of the prolonged pandemic on burnout and mood disorders and to evaluate the influence of positive vaccination beliefs on these factors at a medical center during the extended COVID-19 pandemic. Methods: This retrospective study analyzed the results of an online questionnaire survey including burnout status and mood disorders from 2020 to 2022. The factors related to mood moderate/severe disorders and the impact of the positive vaccine belief were also explored.The initial analysis revealed that healthcare professionals continued to experience significant levels of personal and work-related burnout, along with mood disorders. However, the scores and the percentage of moderate to severe burnout gradually decreased. Notably, the percentage of individuals with moderate to severe mood disorders also gradually declined (2020: 13.4%, 2021: 12.3%, 2022: 11.1%). The number of participants who need professional interventions decreased from 56.2% in 2020 to 45.9% in 2021, and 46% in 2022. Multivariate analysis revealed a positive vaccine belief was associated with a lower risk of moderate/severe mood disorders, with odd ratios (OR) and 95% confidence intervals (95% CI) of 0.38 (0.28 -0.52) and 0.41 (0.30 -0.52) in the 2021 and 2022 cohorts, respectively. Further investigation revealed that age over 50 was linked to a positive vaccine belief in 2021 and 2022. Within the 2022 cohort, working as nurses was identified as the independent factor associated with a less positive belief, with the OR and 95% CI of 0.49 (0.27 -0.90).The findings of the present study suggest burnout and mood disorders are still significant during the pandemic. A positive vaccine belief may mitigate pandemicrelated mental distress. Further interventions to enhance the belief combined with other supporting measures are important in a long fight against the pandemic.